MODEL ANALISIS KINERJA KARYAWAN DAN PENGARUHNYA TERHADAP KEPUASAN NASABAH PADA BNI SYARIAH CABANG MALANG - Frisca Widyananda (Jurnal Ekonomi Pembangunan, 2012)
The research for this thesis investigated by Frisca Widyananda done at PT. BNI Syariah Branch Malang with the title "Model Employee Performance Analysis and its Impact on Customer Satisfaction BNI Syariah Branch Malang" with the kind of research is descriptive qualitative and quantitative descriptive the author outlines back what was seen and heard at the time the research took place and score points obtained in the questionnaire that could eventually be used to solve problems and draw conclusions. The result showed that the number of employees and customers who fill out the study through questionnaires that have been distributed by the authors state that the employee's performance is given to customers at PT. BNI Syariah Branch Malang is good which includes performance, communication, coordination and motivation to work is good enough for our customers.